2014
DOI: 10.1155/2014/218749
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a Low Dose of Estrogen on Antioxidant Defenses and Heart Rate Variability

Abstract: This study tested whether a low dose (40% less than the pharmacological dose of 17-β estradiol) would be as effective as the pharmacological dose to improve cardiovascular parameters and decrease cardiac oxidative stress. Female Wistar rats (n = 9/group) were divided in three groups: (1) ovariectomized (Ovx), (2) ovariectomized animals treated for 21 days with low dose (LE; 0.2 mg), and (3) high dose (HE; 0.5 mg) 17-β estradiol subcutaneously. Hemodynamic assessment and spectral analysis for evaluation of auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 47 publications
3
18
0
Order By: Relevance
“…The present study further supports the role of catalase in our model system because reported studies, including ours, show that E 2 enhances catalase catalytic activity in the heart of female rats (Campos et al., ; El‐Mas and Abdel‐Rahman, ; Ibrahim et al., ; Yao and Abdel‐Rahman, ). Further, acute EtOH causes additional increase in cardiac catalase activity in the presence of E 2 receptor‐alpha activation along with myocardial oxidative stress and dysfunction (Yao and Abdel‐Rahman, ).…”
Section: Discussionsupporting
confidence: 90%
“…The present study further supports the role of catalase in our model system because reported studies, including ours, show that E 2 enhances catalase catalytic activity in the heart of female rats (Campos et al., ; El‐Mas and Abdel‐Rahman, ; Ibrahim et al., ; Yao and Abdel‐Rahman, ). Further, acute EtOH causes additional increase in cardiac catalase activity in the presence of E 2 receptor‐alpha activation along with myocardial oxidative stress and dysfunction (Yao and Abdel‐Rahman, ).…”
Section: Discussionsupporting
confidence: 90%
“…It is important to consider the underlying biochemical environment following the regaining of each individual ER subtype function in OVX rats to understand the basis for their relative contribution to EtOH‐evoked biochemical and hemodynamic effects. While reported studies including ours (Campos et al., ; Ibrahim et al., ; Yao and Abdel‐Rahman, ) showed that E 2 enhances myocardial catalase and mitALDH2 activities in OVX rats, the present study is the first to show that these biochemical effects were only replicated following regaining ERα function (Fig. ).…”
Section: Discussionsupporting
confidence: 49%
“…The catalytic activity of catalase and ALDH2, which serve antioxidant roles (Ma et al., ; Ren et al., ), and catalyze EtOH metabolism (Kinoshita et al., ; Soffia and Penna, ), is enhanced in the presence of E 2 (Campos et al., ), but the ER subtype that mediates these effects in the absence or presence of EtOH is not known. Therefore, these ex vivo studies were conducted to elucidate the effect of selective activation of each of the 3 ER subtypes on myocardial alcohol‐metabolizing enzymes (ADH, CYP2E1, and catalase), antioxidative enzymes (catalase and mitALDH2), and mediators of oxidative stress (MAKs) in the absence or presence of EtOH.…”
Section: Methodsmentioning
confidence: 99%
“…These current findings are important because enhancement of cardiac catalase activity alleviates myocardial oxidative in E 2 treated OVX rats [52], and changes in cellular ER subtype ratios are linked to oxidative stress and antioxidant enzyme activity [53, 54]. Further, similar E 2 beneficial effects on the redox status were reported in female aortas and cardiac tissues [55, 56], and catalase supplementation is linked to improvements in functional recovery of globally ischemic and perfused isolated hearts [57].…”
Section: Discussionmentioning
confidence: 99%